Investigation of the fatigue and dwell-fatigue behavior of the Ti-6Al-4V alloy with Cr/CrN mutilayer coating at room temperature and 350 °C - Fernandes, Martin Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The Ti-6Al-4V alloy is applied in the aerospace industry to produce fan blades and disks of the first stage of gas turbine engines that operate in the temperature range from 20 °C to a temperature range of (250 – 450) °C. During operation, these components are exposed to airborne particles and environmental deterioration responsible for wear, erosion, corrosion and oxidation damage mechanisms. Based on the recent literature, the Cr/CrN multilayer coating improves the corrosion and wear resistance of titanium alloys. However, coatings can be detrimental to the fatigue properties of Ti alloys such as Ti-6Al-4V. The present work aims to investigate the fatigue behavior of the uncoated and Cr/CrN multilayer coated Ti-6Al-4V alloy. The first part of the project was performed with an equiaxed microstructure Ti-6Al-4V alloy substrate and Cr/CrN coating with 8 bilayers (16 layers). The second part of the project was performed with a lamellar Ti-6Al-4V alloy substrate and Cr/CrN coating with 3 bilayers (6 layers). Characterization of crack initiation sites was carried out using SEM and EBSD to identify microstructural configurations prone to crack nucleation and clarify damage mechanisms for the different conditions. In addition, interrupted fatigue tests and in situ tensile tests inside of a scanning electron microscope were performed to elucidate the role played by the coating. The fatigue and dwell-fatigue mechanisms of crack nucleation and the damage mechanisms of the Cr/CrN coating were extensively investigated. The results showed that the coating thickness and number of layers played a role in the fatigue behavior of Ti-6Al-4V alloy since the Cr/CrN coating with 8 bilayers and 5 µm significantly reduced the fatigue strength, while the Cr/CrN coating with 3 bilayers and 1.5 µm nearly maintained the fatigue properties at room temperature. However, the Cr/CrN coating with 3 bilayers also reduced the fatigue life of the titanium alloy at 350°C. Cumulated plastic strain both for fatigue and dwell-fatigue tests were associated with the fatigue mechanism that led to crack initiation, and dwell-fatigue cycles were associated with higher cumulated plastic strain than fatigue cycles. EBSD analysis of the crack nucleation sites revealed that the ⟨𝑎1⟩ and ⟨𝑎2⟩ basal slip systems were responsible for the fatigue crack initiation of the lamellar Ti-6Al-4V alloy both at room temperature and 350°C for the uncoated and coated alloy. The early stages of damage in the coating were identified through in situ tensile tests inside of a SEM.

A liga Ti-6Al-4V é aplicada na indústria aeroespacial para produzir pás e discos do primeiro estágio de motores de turbina a gás que operam de 20 °C a um intervalo de temperaturas de (250 – 450) °C. Durante operação, estes componentes estão expostos a partículas em suspensão e deterioração ambiental responsáveis por mecanismos de dano de desgaste, erosão, corrosão e oxidação. Baseado na literatura recente, o revestimento Cr/CrN de múltiplas camadas melhora a resistência à corrosão e desgaste de ligas de titânio. Contudo, revestimento podem ser prejudiciais às propriedades de fadiga de ligas de Ti como a liga Ti-6Al-4V. O presente trabalho tem o objetivo de investigar o comportamento em fadiga da liga Ti-6Al-4V não recoberta e com recobrimento Cr/CrN de múltiplas camadas. A primeira parte do projeto foi realizada com a liga Ti-6Al-4V equiaxial e um revestimento Cr/CrN com 8 bicamadas (16 camadas). A segunda parte do projeto foi realizada com a liga Ti-6Al-4V lamelar e recobrimento Cr/CrN com 3 bicamadas (6 camadas). A caracterização dos locais de nucleação de trincas foi realizada usando MEV e EBSD para identificar as configurações microestruturais propensas a nucleação de trincas e clarificar os mecanismos de danos para as diferentes condições. Além disso, ensaios de fadiga interrompidos e ensaios de tração in situ dentro de um microscópio eletrônico de varredura foram realizados para elucidar o papel desempenhado pelo revestimento. Os mecanismos de fadiga e de fadiga com período dwell para nucleação de trinca e os mecanismos de dano do revestimento Cr/CrN foram extensivamente investigados. Os resultados mostraram que a espessura do revestimento e o número de camadas influenciaram o comportamento em fadiga da liga Ti-6Al-4V pois o revestimento Cr/CrN com 8 bicamadas e 5 µm reduziu significativamente a resistência à fadiga, enquanto o revestimento Cr/CrN com 3 bicamadas e 1,5 µm manteve aproximadamente as propriedades de fadiga em temperatura ambiente. Contudo, o revestimento Cr/CrN com 3 bicamadas também reduziu a vida em fadiga da liga de titânio na temperatura de 350°C. A deformação plástica acumulada para ambos os ensaios de fadiga e fadiga com dwell foram associados com maiores deformações plásticas do que ciclos de fadiga. A análise EBSD dos locais de nucleação de trinca revelaram que os sistemas de deslizamento basais ⟨𝑎1⟩ e ⟨𝑎2⟩ foram responsáveis pela nucleação de trincas de fadiga na liga Ti-6Al-4V com microestrutura lamelar na temperatura ambiente e 350°C. Os estágios iniciais de dano no revestimento foram identificados através de ensaios de tração in situ em um MEV.
Investigação do comportamento em fadiga e do efeito dwell da liga Ti-6Al-4V com revestimento Cr/CrN de múltiplas camadas na temperatura ambiente e 350 °C
Keywords: Titanium alloys; Fatigue; Dwell-fatigue; Surface treatments; Ti-6Al-4V; Cr/CrN coating; Ligas de titânio; Fadiga; Dwell-fadiga; Tratamentos superficiais; Ti-6Al-4V; Revestimento Cr/CrN; Metais - Fadiga; Materiais - Fadiga; Mecânica da fratura